The impact of psychological personality traits on the health development of school-aged children in the educational process - KYRYCHUK, Valeriy; RUDENKO, Serhiy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. The influence of psychological personality traits (PPT) on the health formation of school-aged children in extreme social environments is increasing, making its study essential from both theoretical and practical perspectives for enhancing the healthcare system. Methods. A randomized controlled study involving 1,110 patients aged 9-17 years was conducted using a double-blind method. The study examined the dynamics of health formation in school-aged children influenced by issues stemming from established psychological personality traits (anxiety, aggressiveness, insecurity, impulsiveness, asociality, introversion, externality, and aesthetic insensitivity). Data collection and processing were conducted using the automated project system Universal online, version 45. Results. The study explored the impact of established psychological personality traits (impulsivity, aggressiveness, insecurity, externality, dishonesty, asociality, and aesthetic insensitivity) on the development of respiratory and digestive system diseases. It was found that anxiety is a significant risk factor for the development of digestive system diseases (DSD) – OR = 2.16, indicating more than a twofold increased risk of disease development among individuals with anxiety, though not for respiratory system diseases (RSD) – OR = 1.29, where this risk is not statistically significant. Dishonesty is identified as risk factor for respiratory system diseases. Asociality is a notable risk factor for both types of diseases, with its impact on DSD being slightly stronger (OR = 1.89, 95% CI: 1.23–2.91, p < 0.05) compared to RSD – OR = 1.53, 95% CI: 1.00–2.36, p < 0.05, indicating that asociality is an important risk factor for the formation of both respiratory and digestive system diseases, necessitating consideration of this characteristic in the prevention of both types of diseases. Conclusions. The impact of established psychological personality traits (PPT) on the development of respiratory and digestive system diseases in school-aged children during their education has been recognized. If not promptly identified, the detrimental influence of PPT may lead to systemic dysfunctions due to atypical clinical forms of respiratory and digestive system diseases. Special attention should be given to addressing manifestations of anxiety, dishonesty, and asociality. Enhancing the overall health in children may alleviate social issues, improve social adaptation, and boost academic performance.